Dreams, Sleep, and Psychotropic Drugs - Nicolas, Alain; Ruby, Perrine M. (Frontiers in Neurology, 2020)
Over the past 60 years, the impact of psychotropic drugs on dream recall and content has been scarcely explored. A review of the few existing experimental results on the topic, lead us to the following conclusions. For antidepressant drugs, in the great majority, they reduce dream recall frequency (DRF) and the improvement of depressive symptoms is associated with an increase of positive emotion in dream content. For sedative psychotropic drugs, their improvement of sleep quality is associated with a reduction of DRF, but the effect on dream content is less clear. Few occurrences of nightmare frequency increase have been reported, with intake of molecules disturbing sleep or with the withdrawal of some psychotropic drugs. Importantly, the impact of psychotropic drugs on REM sleep does not explain DRF modulations. The reduction of intra-sleep awakenings seems to be the parameter explaining best the modulation of DRF by psychotropic drugs. Indeed, molecules which improve sleep continuity by reducing intra-sleep awakenings, also reduce the frequency of dream recall, which is coherent with the “arousal-retrieval model” stating that night-time awakenings enable dreams to be encoded into long term memory and therefore facilitate dream recall. DRF is nonetheless influenced by several other factors (e.g. interest in dreams, the method of awakening, personality traits) which may explain a large part of the variability of results observed and cited in this article.